Donor site selection and clinical outcomes of nipple–areola skin-sparing mastectomy with immediate autologous free flap reconstruction: A single-institution experience. Issue 3 (March 2016) - Fujimoto, H.; Ishikawa, T.; Satake, T.; Ko, S.; Shimizu, D.; Narui, K.; Yamada, A.; Sasaki, T.; Nagashima, T.; Endo, I.; Miyazaki, M.
Abstract: Background: The objective of this study was to examine the clinical outcomes of immediate breast reconstruction using perforator flaps from different donor sites, and to characterize the trends among these flaps. Methods: We retrospectively reviewed 136 consecutive patients who underwent immediate breast reconstruction using free flaps after skin-sparing mastectomy (SSM) or nipple-sparing mastectomy (NSM). The whole breast was pathologically analyzed in 5-mm sections. Breast reconstruction was performed using the deep inferior epigastric perforator (DIEP) flap, gluteal artery perforator (GAP) flap, and posterior medial thigh perforator (PMTP) flap. Patient characteristics were compared among donor sites. Results: NSM was converted to SSM because of intraoperative subareolar tumor positivity in 7 of 107 patients. Eleven patients had positive margins in permanent sections. All but one patient had a positive horizontal margin in the peripheral direction. The 5-year recurrence-free survival rate was 91.9%. The locoregional recurrence rate was 5.1% with a mean follow-up observation period of 75 months. DEIP, GAP, and PMTP flaps were used in 64 (47.1%), 38 (27.9%), and 34 (25.0%) patients, retrospectively. DIEP flaps were used in older patients and those with a higher body mass index. GAP flaps were used in younger patients. DIEP and GAP flaps were used for larger breasts, and PMTP flaps for smaller breasts. Conclusion: NSM or SSM with immediate perforator flap breast reconstruction is an oncologically acceptable surgical option. We believe that age, desire to have children, body mass index, and excised breast volume are valuable factors for selecting the optimal donor site.